Pediatric Medical Traumatic Stress in Inflammatory Bowel Disease, Pancreatitis, and Cystic Fibrosis. Issue 4 (25th July 2022) - Cuneo, Addison A.; Abu-El-Haija, Maisam; Marsac, Meghan L.; Verstraete, Sofia; Heyman, Melvin B.; Ly, Ngoc; Perito, Emily R.
Abstract : Objectives: Known as pediatric medical traumatic stress (PMTS), posttraumatic stress symptoms from medical experiences have not been explored in children with chronic gastrointestinal diseases. This cross-sectional study of children and adolescents with inflammatory bowel disease, chronic pancreatitis and cystic fibrosis, aimed to (1) estimate the prevalence of medical potentially traumatic events (PTEs) and PMTS, (2) explore potential risk factors for PMTS, and (3) explore potential consequences of PMTS. Methods: This cross-sectional study used validated, self-report measures to evaluate PTEs and PMTS. Descriptive statistics and regression analyses were used to achieve study objectives. Results: Over two-thirds of children reported a medical potentially traumatic event (91 of 132, 69%). Forty-eight had PMTS symptoms (36%). PMTS was associated with medication burden, emergency and intensive care visits, and parent posttraumatic stress disorder in multivariate analysis. Potential consequences associated with PMTS included school absenteeism, home opioid use, poor quality of life, and parent missed work. Conclusions: A substantial portion of our cohort reported medical PTEs and PMTS. The exploratory analysis identified potential associations between PMTS and illness factors, parent posttraumatic stress disorder, and functional impairments. Further studies of PMTS detection, prevention and treatment are integral to optimizing these children's health and quality of life.